INTERKULTURALISME DALAM SASTRA WARNA LOKAL BALI DAN RELEVANSINYA SEBAGAI BAHAN AJAR SASTRA UNTUK MENDUKUNG PENCEGAHAN INTOLERANSI DI SEKOLAH - I Made, Sujaya; Liswahyuningsih, Ni Luh Gede; Dwipayana, I Kadek Adhi (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2025)
This article reveals interculturalism in local Balinese Indonesian literature and its relevance as literary teaching materials to support the prevention of intolerance in schools. This research is motivated by the fact that diversity is an empirical fact of Indonesian society that can have a positive impact as a social and cultural strength of the nation, but can also have a negative impact because it has the potential to cause social conflict. The potential for social conflict usually arises from intolerant attitudes in society, including in the school environment. This indicates that intercultural awareness must continue to be fostered. As a cultural product as well as a cultural practice, literature can play a role in strengthening students' intercultural awareness. Therefore, literary learning requires teaching materials that are relevant and contextual to the needs of building students' intercultural awareness. On that basis, research on interculturalism in local Balinese literature is important to conduct. Local Balinese literature was chosen as the focus of the research because the results of this research are expected to be applied in Bali as an open area with the complexity of typical intercultural problems. The main problems to be answered in this research are the representation of interculturalism in local Balinese literature and its relevance as literary teaching materials to support the prevention of intolerance in schools. This research uses a qualitative descriptive design with a sociology of literature approach. The research data source is in the form of local Balinese Indonesian literature containing intercultural elements. The results of the study found that interculturalism in local Balinese Indonesian literature is woven through the medium of marriage and friendship institutions. The meeting of two different cultures gives rise to cultural shock which is responded to with adaptive and accommodating attitudes of the story characters. In the relationship between characters who have different backgrounds, there are a number of factors that allow interculturalism to occur, namely economy, religion, and tradition. However, this study found a tendency for religion to be a separating factor, while customs and traditions are unifying factors.